Cat Scratch Disease: The Story Continues - Mary Anne Opavsky (Canadian Journal of Infectious Diseases)
OBJECTIVE: To present a perspective on the current state of knowledge of cat scratch disease (CSD), including the evidence for Bartonella henselae as the etiological agent, epidemiological and clinical characteristics of the disease, available diagnostic tests and current therapeutic options.